Clonal, Plasmidic and Genetic Diversity of Multi-Drug-Resistant Enterobacterales from Hospitalized Patients in Tripoli, Libya - Nada Elgriw; Véronique Métayer; Antoine Drapeau; Pauline François; Sana Azaiez; Maha Mastouri; Hajer Rhim; Adam Elzagheid; Najeeb Soufiyah; Jean-Yves Madec; Cherifa Chaouch; Wejdene Mansour; et al. (MDPI AG, 2023)
Resistance to extended-spectrum cephalosporins (ESC) and carbapenems in Enterobacterales is a major issue in public health. Carbapenem resistance in particular is associated with increased morbidity and mortality. Moreover, such resistance is often co-harbored with resistance to non-beta-lactam antibiotics, and pathogens quickly become multi-drug-resistant (MDR). Only a few studies have been published on AMR in Libyan hospitals, but all reported worrisome results. Here, we studied 54 MDR isolates that were collected from 49 patients at the Tripoli University Hospital between 2019 and 2021. They were characterized using phenotypic methods, PCR and PFGE, and a sub-set of isolates were short- and long-read whole-genome sequenced. The results showed the frequent occurrence of Klebsiella pneumoniae (49/54), among which several high-risk clones were responsible for the spread of resistance, namely, ST11, ST17, ST101 and ST147. ESC and carbapenem resistance was due to a wide variety of enzymes (CTX-M, OXA-48, NDM, KPC), with their corresponding genes carried by different plasmids, including IncF-IncHI2 and IncF-IncR hybrids. This study highlights that implementation of infection prevention, control and surveillance measures are needed in Libya to fight against AMR.